Are genetic variations in IL‐21–IL‐23R–IL‐17A cytokine axis involved in a pathogenic pathway of rheumatoid arthritis? Bayesian hierarchical meta‐analysis. Issue 10 (28th March 2019) - Mohammadi, Fatemeh Sadat; Aslani, Saeed; Mostafaei, Shayan; Jamshidi, Ahmadreza; Riahi, Parisa; Mahmoudi, Mahdi
Abstract: Inflammatory cytokines have been established to be involved in the pathogenesis of rheumatoid arthritis (RA). The genetic polymorphisms in the interleukin (IL) 23 receptor (IL23R), IL21, and IL17 have been associated with RA risk. However, there is no conclusive understanding of the genes encoding the immunoinflammatory IL‐21–IL‐23R–IL‐17A pathway in RA aetiopathogenesis. This meta‐analysis was conducted to attain this goal. A comprehensive literature search was conducted in Scopus and PubMed to look for the relevant case–control studies up until 2018. A Bayesian hierarchical meta‐analysis was carried out to assess the association between the polymorphisms and the risk of RA. The association was estimated by calculating the logarithm of odds ratio (Log OR) and 95% credible interval (95% CI). In this meta‐analysis, 37 case–control studies comprising 23, 506 RA patients and 25, 984 healthy individuals were found for analyzing the IL23R, IL21, and IL1A gene polymorphism and risk of RA. In the IL23R gene rs1343151 SNP, the minor A allele significantly increased the risk of RA (Log OR = 0.085, 95% CI = 0.008, 0.156). Moreover, the minor AA genotype was significantly associated with increased RA risk (Log OR = 0.176, 95% CI = 0.028, 0.321). In addition, the C allele of the IL23R gene rs2201841 SNP significantly decreased the disease risk (Log OR = −0.544, 95% CI = −1.0, −0.065). Since Bayesian meta‐analysis is a powerful strategy to pool the data, it can be mentioned that genetic polymorphisms of IL23R, but not IL21 and IL17A, are involved in susceptibility to RA. Abstract : Bayesian meta‐analysis is a powerful strategy to pool the data and it can be mentioned that genetic polymorphisms of interleukin (IL) 23 receptor (IL23R), except IL21 and IL17A, are involved in susceptibility to rheumatoid arthritis.